From shared decision making to patient-centered decision making - Fineberg Harvey V (BMC, 2012)
Abstract Shared decision making involving patients and physicians has gained adherents in Israel and other countries and has many virtues. This commentary argues that medical decision making should ideally be shaped by the particular needs and preferences of the patient, which may be to share in decision making, or at times call for a physician to assume full responsibility for decisions or, at the other extreme, to support and guide a patient who wishes to decide autonomously on what to do. This is a commentary on http://www.ijhpr.org/content/1/1/5/